Health Mitigation Strategies and Challenges in Vulnerable Groups and Natives in Indonesia: A Literature Review - Tanadi, Aristo; Basrowi, Ray Wagiu (ILUNI MKK FKUI and PRODI MKK FKUI, 2023)
Introduction: Indonesia, like many other countries, has vulnerable groups and natives that are at higher risk for poor health outcomes due to social, economic, and health disparities. Health mitigation efforts targeting these groups are crucial to ensure equitable health outcomes in Indonesia. This literature review aims to assess the current evidence on health mitigation in vulnerable groups and natives in Indonesia.Methods: We conducted a comprehensive search of the literature using databases such as PubMed, Scopus, and Google Scholar. We searched using a combination of keywords and controlled vocabulary terms related to vulnerable groups, natives, health mitigation, and Indonesia to identify relevant articles. We included articles published from 2013 to 2023 that focused on health mitigation in vulnerable groups and natives in Indonesia. We excluded articles that did not focus on vulnerable groups or natives, were not related to health mitigation, or were not based in Indonesia.Results: Our search yielded 11 relevant articles, including both original research and review articles. The studies focused on a range of vulnerable groups and natives, including older adults, women, children, refugees, and transgender people. Most barriers that were faced were difficulty to access health care providers, financial constraints, lack of knowledge regarding certain health issues, and social and cultural factors. Most study found that community-based health interventions, such as providing health education and access to health services, were more likely to be effective in improving health outcomes among vulnerable groups in Indonesia.Conclusion: In conclusion, this literature review highlights the need for continued efforts to mitigate health disparities in vulnerable groups and natives in Indonesia. Community-based health interventions and tailored health programs show promise, but cultural and social barriers to healthcare access must also be addressed to ensure equitable health outcomes.